Improving Learning Outcomes in Islamic Religious Education Using Direct Instruction Method Based on Interactive Digital Media at Private High School Harapan Bangsa Kuala - Putri, Anggi Seprina; Tanjung, Alfian (Jurnal Riset Ilmu Pendidikan, 2025)
This research aims to improve the learning outcomes of class X students in Islamic religious education subjects at Harapan Bangsa Kuala Private High School through the application of a direct instruction learning model based on interactive digital media. This research is semi-qualitative Class Action Research with two cycles. Each cycle consists of planning, action, observation, evaluation and reflection. The data sources used are primary data and secondary data. Primary data comes from teachers and students. Secondary data comes from documents used in research. Data collection techniques through observation, interviews, documentation and performance training. Data analysis techniques use critical analysis techniques and comparative descriptive statistical techniques. The results of this research show that student learning outcomes have increased in each cycle. Before implementing the action, student learning outcomes which were completed with the results of observations regarding teacher teaching activities and student learning activities in cycle 2 showed improvement. The achievement of teacher teaching activities was 94.45% with very good criteria. Achievement of student learning activities was 88.89% with good criteria. Learning results in cycle 2 show that all students can achieve KMKTP. The highest score obtained by students was 100 with a total of 6 students, while the lowest score was 80 with a total of 8 students. The average score in cycle 2 was 89.29.